2006
DOI: 10.1111/j.1468-3148.2005.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Workers with an Intellectual Disability in Supported Employment

Abstract: AimThis study investigate what characteristics of supported employment increase quality of life and whether quality of life is higher in supported employment workers or the sheltered ones in Spain. Typicalness, the degree to which the characteristics of a job are the same as those of co-workers without a disability in the same company, was considered as one of the supported employment characteristics in the analysis. Method Two groups were put together to obtain the data using two questionnaires that were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
13
1
3
Order By: Relevance
“…This is supported by the findings here that the highest rates of emotional or mental health were associated with engagement in employment. Findings that employment is superior to other forms of occupational activity support similar previous findings (Kober & Eggleton, ) and disagree with studies that found no such outcome differences (Verdugo et al, ). Our findings that day services and home activation were also associated with significantly better rates of emotional or mental health, compared with not being engaged in any such activity, add to the existing literature.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This is supported by the findings here that the highest rates of emotional or mental health were associated with engagement in employment. Findings that employment is superior to other forms of occupational activity support similar previous findings (Kober & Eggleton, ) and disagree with studies that found no such outcome differences (Verdugo et al, ). Our findings that day services and home activation were also associated with significantly better rates of emotional or mental health, compared with not being engaged in any such activity, add to the existing literature.…”
Section: Discussioncontrasting
confidence: 52%
“…When people with intellectual disability are employed, studies have also shown them to report a higher quality of life than unemployed counterparts (Eggleton, Robertson, Ryan, & Kober, ; Kober & Eggleton, ). However, the literature is inconclusive on whether there are differences in quality‐of‐life outcomes between people with intellectual disability in different occupational settings (Kober & Eggleton, ) or no differences (Verdugo, Jordán de Urríes, Jenaro, Caballo, & Crespo, ).…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años encontramos estudios que evalúan y valoran dicha calidad de vida, tanto desde una perspectiva objetiva como subjetiva (Verdugo, 2006;Beyer, 2010). Rollins, Bond, Jones, Kukla y Collins (2011) estudian la importancia de las redes sociales establecidas en el centro de trabajo entre los empleados con enfermedades mentales severas.…”
Section: Abstract: It Is the Function Of Special Needs Employment Cenunclassified
“…Moreover, competitive employment contexts allow people with disability to work alongside non‐disabled individuals and to reap the same benefits, such as standard wages and contracts as these other workers, in similar jobs for the same business (Verdugo et al . ).…”
Section: Introductionmentioning
confidence: 97%